Waste Management at the Local Level in the EU and Ukraine - Ladychenko, Viktor; Melnychuk, Olha; Golovko, Liudmyla; Burmak, Oksana (European Journal of Sustainable Development, 2020)
The purpose of this article is to provide an overview of theoretical and practical issues related to the implementation of the responsibilities of bodies of local self-government for the management of solid municipal waste according to the Waste Framework Directive. Experience of EU Member States in this sphere was studied. The state of adaptation of Ukrainian legislation to the requirements of the European Union in the field of waste management has been investigated and proposals for implementation of experience of EU member states were made. Keywords: EU waste policy, EU law, waste management, municipal waste, adaptation of Ukrainian legislation to EU law